Effects of Ethrel on Organogenesis of Protocorm-like bodies in Dendrobium kingianum In vitro - Habiba, Sultana Umma; Ahasan, Md Monjurul; Shimasaki, Kazuhiko (Plant Tissue Culture and Biotechnology, 2018)
Abstract not available Plant Tissue Cult. & Biotech. 28(1): 141-146, 2018 (June)